Drug Utilization Pattern and Cost Analysis of Drugs used at Dermatology Out Patient Department in a Tertiary Care Hospital - Anita Yadav,; Birendra Kumar Yadav,; Pradip Chhetri, (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTIONThe irrational prescription of drugs is highly prevalent among patients suffering from skin diseases. Since it has a serious impact on health and economy, there is an urgent need to study drug utilization pattern in hospital settings. Therefore, this study aims to investigate drug utilization pattern and its cost analysis in Dermatology Out Patient Department in a tertiary care teaching hospital.MATERIAL AND METHODSA four-month, prospective, cross-sectional descriptive study was conducted from 10th February 2022 to 10th June 2022 in newly diagnosed cases attending Out Patient Department of dermatology at Universal College of Medical Sciences, Bhairahawa, Nepal. Ethical approval was obtained from the Institutional Review Committee (UCMS/IRC/037/22). Purposive consecutive sampling technique was used. The data were collected from patient cards and details were ﬁlled in predesigned proforma. The collected data were analyzed in Statistical Package for Social Sciences version 20.RESULTSA total of 601 prescriptions were scrutinized. The common skin condition found was eczema (9.98%) while the common classes of drugs prescribed were antifungals (31.94%). The number of drugs per prescription varied from one to ﬁve with an average of 3.11. It was observed that 3.95% of prescription was by generic names. The maximum of drugs (36.06%) was prescribed in tablet form. The percentage of antibiotics prescribed and drugs prescribed from the WHO Essential Drugs List were 12.31% and 27.88% respectively. The average cost per prescription calculated was 739.39 Nepali Rupees.CONCLUSIONA drug utilization study can help to rationalize prescriptions, reduce errors, and improve cost-effective treatment.